Johanna Reich : the presence of absence - videos. - Smolik, Noemi; Kunstmuseum Ahlen, Münster (Münster : GWK, 2011)
Reich, Johanna
Johanna Reich : the presence of absence, Kunstmuseum Ahlen, Münster, 11.09 bis 31.10.2010
kunstcatalogus